2017
DOI: 10.1161/jaha.117.005707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D on Blood Pressure, Arterial Stiffness, and Cardiac Function in Older People After 1 Year: BEST‐D (Biochemical Efficacy and Safety Trial of Vitamin D)

Abstract: BackgroundThe relevance of vitamin D for prevention of cardiovascular disease is uncertain. The BEST‐D (Biochemical Efficacy and Safety Trial of vitamin D) trial previously reported effects of vitamin D on plasma markers of vitamin D status, and the present report describes the effects on blood pressure, heart rate, arterial stiffness, and cardiac function.Methods and ResultsThis was a randomized, double‐blind, placebo‐controlled trial of 305 older people living in United Kingdom, who were allocated vitamin D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…One further recent meta‐analysis, examining only FMD, showed a slightly greater benefit (treatment effect of vitamin D was 1.27% for FMD), perhaps attributable to differences in both study selection and the data used; our analysis had the benefit of access to IPD, which allowed us to verify the accuracy of published data and data used in previous meta‐analyses. The results are also consistent with recent data suggesting no effect of vitamin D supplementation on plasma N‐terminal pro‐B‐type natriuretic peptide levels or echocardiographic indices in older people after 12 months of therapy …”
Section: Discussionsupporting
confidence: 92%
“…One further recent meta‐analysis, examining only FMD, showed a slightly greater benefit (treatment effect of vitamin D was 1.27% for FMD), perhaps attributable to differences in both study selection and the data used; our analysis had the benefit of access to IPD, which allowed us to verify the accuracy of published data and data used in previous meta‐analyses. The results are also consistent with recent data suggesting no effect of vitamin D supplementation on plasma N‐terminal pro‐B‐type natriuretic peptide levels or echocardiographic indices in older people after 12 months of therapy …”
Section: Discussionsupporting
confidence: 92%
“…Table 1 summarizes the characteristics of the included RCTs. The RCTs were conducted in different continents: Asia 23 , Europe 19 22 , 25 27 , America 17 , and Oceania 18 . All were placebo controlled and published in English.…”
Section: Resultsmentioning
confidence: 99%
“…Al-Dujalili et al also highlighted an effect of vitamin D consumption on both systolic and diastolic blood pressure [35]. In contrast, some studies have shown no beneficial relationships in this context [36][37][38][39][40]. For example, Salekzamani et al showed that supplementation with high-dose vitamin D for 4 months was not correlated with blood pressure [41].…”
Section: Discussionmentioning
confidence: 99%